A colloidal gold-based lateral flow immunoassay for direct determination of haemoglobin A1c in whole blood - Ang, S.H.; Yu, C.Y.; Ang, G.Y.; Chan, Y.Y.; Alias, Y.; Khor, S.M. (2015)
We developed an immunosensor that operates based on the lateral flow principle designed to detect haemoglobin A1c (HbA1c), a biomarker for type 2 diabetes mellitus in human blood samples. Two different clones of antibodies were used to form a "sandwich" when HbA1c was present. Functionalization of colloidal gold with antibodies was carefully optimized to generate stable gold conjugates to amplify the signal from the formed "sandwich" for the immunoassay. The ideal blocking reagent to minimize background noises, the test line format on the strip, the selectivity of the assay towards HbA1c against HbA0 and glycated species of HbA0, and the potential interference contributed by the colour of the blood sample were investigated. Captured HbA1c on the lateral flow immunosensor can be distinguished based on the number and intensity of the test lines shown; visual detection of the lines shown then indicated the distinctive groups at normal, under control, and elevated levels of HbA1c. Also, a calibration curve that covered the detection range of 4 (20 mmol mol-1) and 12 (108 mmol mol-1) HbA1c was reported, indicating that the prototype can be used for future quantification utilizing a lateral flow reader. The resultant immunosensor was found to report results that were easier to be interpreted and relatively inexpensive compared to electrochemical biosensors developed for the detection of HbA1c.